Effect of Square Mesh Panels on Catches of Stationary Bag Net in Hooghly Estuary - K.C., Dora; E., Kathavarayan; C.K., Mukherjee (Fishery Technology, 2025)
Effect of incorporation of square mesh panels in stationary bag nets operated in Hooghly estuary (West Bengal) on fish landings was studied through comparative fishing experiments. The results showed that catches of juveniles of prawns and finfishes was significantly lower in the experimental gear with square mesh panels of 20 mm bar mesh size, compared to the control net. 50% retention lengths (L ) of Metapenaeus sp. and Macrobrachium mirable, Macrobrachium lamerri and sciaenids were also higher in the experimental bag net compared to the control net. Results indicated that provision of square mesh panels in bag nets would help in the conservation and management of estuarine fishery resources